No Planet for Apes? Assessing Global Priority Areas and Species Affected by Linear Infrastructures - Ascensão, Fernando (2022)
Approximately 65% of primate species are facing extinction, with threats including the impacts of linear infrastructures such as roads, railways, and power lines, associated with habitat loss and fragmentation, direct and indirect mortality, and changes in animal behavioral patterns. Nevertheless, this is an often-overlooked topic in primatology, and there is limited information on which regions and species are most affected by linear infrastructures. Here, we provide a global assessment of priority areas and primate species for conservation by integrating information from global-scale open-access data sets on the distributional ranges, traits, and threats to primate species and linear infrastructures, together with a systematic literature review and a questionnaire sent to primatological societies. We produced a bivariate map that reflects the patterns of co-occurrence of the Conservation Value and Infrastructure Density. From this map we highlight Primate Mitigation Areas (regions with high Primate Conservation Value and Infrastructure Density), which are areas where infrastructure mitigation should be prioritized; and the Primate Preservation Areas (regions with high Primate Conservation Value and low Infrastructure Density), which represent areas that should be preserved from further infrastructure development. Primate Mitigation Areas primarily include the Atlantic forest of Brazil, the Guinean forests of West Africa, and most of Southeastern Asia, whereas Primate Preservation Areas are found principally in the Amazon and Congo River basins. Our assessment also produced a list of priority species affected by infrastructures, with the great apes and gibbons ranking highest. Global infrastructure projects, especially the Belt and Road Initiative, can seriously affect both priority areas (particularly preservation areas) and the most vulnerable species, due to the massive sprawl of linear infrastructures and associated human activity. Thus, we call for dedicated strategic environmental and social assessments throughout these different economic corridors within the Belt and Road Initiative planning process, prior to developing the different projects. Our assessment can serve as a tool to coordinate management actions and legislation around the world.